New user? Sign up

Existing user? Log in

If \(\cos^2(x) + \cos^4(x) = 1\), prove that \(\tan^2(x) + \tan^4(x) = 1\).

Note by Rishit Joshi 4 years, 8 months ago

Easy Math Editor

*italics*

_italics_

**bold**

__bold__

- bulleted- list

1. numbered2. list

paragraph 1paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)

> This is a quote

This is a quote

# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"

2 \times 3

2^{34}

a_{i-1}

\frac{2}{3}

\sqrt{2}

\sum_{i=1}^3

\sin \theta

\boxed{123}

Sort by:

Divide both sides by \( \cos^2 (x) \)

\(1 + \cos^2 (x) = \sec^2 (x) \)

\(1 + \cos^2 (x) = \tan^2 (x) + 1 \)

\( \cos^2 (x) = \tan^2 (x) \)

\( \frac {1}{ \sec^2 (x) } = \tan^2 (x) \)

\( \frac {1}{ \tan^2 (x) + 1 } = \tan^2 (x) \)

\(1 = \tan^2 (x) (\tan^2 (x) + 1 ) \)

\( \tan^4 (x) + \tan^2 (x) = 1 \)

Log in to reply

I was complete at the step \( cos^2(x) = tan^2(x) \) . The next steps weren't required. You just had to replace \( cos^2(x)\) by \(tan^2(x) \) in the given equation.

can u explain me

IN THE FIRST STEP I DIDN 'T GOT HOW 1+COS^2X CAME CAN U EXPLAIN ME AGAIN PLSS

Let \(cos^2 x = t\) \(\Rightarrow t^2 + t - 1 = 0\) \(\Rightarrow t = \frac{\sqrt{5} - 1}{2}\) and \(\frac{-\sqrt{5} - 1}{2}\)

Since ,\(0 \leq t \leq 1\) \(\Rightarrow cos^2x = \frac{\sqrt{5} - 1}{2}\) , \(\Rightarrow sec^2 x = \frac{2}{\sqrt{5} - 1}\) = \(\frac{\sqrt{5} + 1}{2}\) ,\( tan^2 x = sec^2x - 1 = \frac{\sqrt{5} - 1}{2} = cos^2x\)

\(\Rightarrow tan^2x + tan^4x = cos^2x + cos^4x =1 \)

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestDivide both sides by \( \cos^2 (x) \)

\(1 + \cos^2 (x) = \sec^2 (x) \)

\(1 + \cos^2 (x) = \tan^2 (x) + 1 \)

\( \cos^2 (x) = \tan^2 (x) \)

\( \frac {1}{ \sec^2 (x) } = \tan^2 (x) \)

\( \frac {1}{ \tan^2 (x) + 1 } = \tan^2 (x) \)

\(1 = \tan^2 (x) (\tan^2 (x) + 1 ) \)

\( \tan^4 (x) + \tan^2 (x) = 1 \)

Log in to reply

I was complete at the step \( cos^2(x) = tan^2(x) \) . The next steps weren't required. You just had to replace \( cos^2(x)\) by \(tan^2(x) \) in the given equation.

Log in to reply

can u explain me

Log in to reply

IN THE FIRST STEP I DIDN 'T GOT HOW 1+COS^2X CAME CAN U EXPLAIN ME AGAIN PLSS

Log in to reply

Let \(cos^2 x = t\) \(\Rightarrow t^2 + t - 1 = 0\) \(\Rightarrow t = \frac{\sqrt{5} - 1}{2}\) and \(\frac{-\sqrt{5} - 1}{2}\)

Since ,\(0 \leq t \leq 1\) \(\Rightarrow cos^2x = \frac{\sqrt{5} - 1}{2}\) , \(\Rightarrow sec^2 x = \frac{2}{\sqrt{5} - 1}\) = \(\frac{\sqrt{5} + 1}{2}\) ,\( tan^2 x = sec^2x - 1 = \frac{\sqrt{5} - 1}{2} = cos^2x\)

\(\Rightarrow tan^2x + tan^4x = cos^2x + cos^4x =1 \)

Log in to reply